Perception of professional nursing on the companion of inclusion in the process of parturition - Milena Gabriela dos Santos Silva; Alexandra do Nascimento Cassiano; Flávia Andréia Pereira Soares dos Santos; Amandda Thaise de Sousa Barbosa; Bertha Cruz Enders; Nilba Lima de Souza; Flávio Lopes Alves (Universidad de Alicante, 2017)
The research aimed to identify the nursing knowledge about the insertion of companion in the parturition process. exploratory and descriptive study with qualitative approach developed in a university hospital in the city of Santa Cruz, Rio Grande do Norte, Brazil. The number of participants was determined by saturation data, respecting the inclusion and exclusion criteria. Data were collected through a semi-structured interview, later worked according to content analysis according to Bardin and analyzed according to the principles of symbolic interactionism of Blumer. The escort was valued for its importance, which runs through the emotional support, joint participation and rights guaranteed by law. However, factors linked to the lack of knowledge, inexperience and curiosity were found to be factors that may compromise the care routine. Nursing professionals recognize the importance of accompanying, which moves through the emotional support, guidance and co-participation in right guaranteed by law.